The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jtcvs.2013.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Results of elective repair at 6 months or younger in 277 patients with tetralogy of Fallot: A 14-year experience at a single center

Abstract: Elective tetralogy of Fallot repair was performed at 6 months or younger with low morbidity, no hospital mortality, and an 11.6% complication rate. Longer support times, lower weight, chromosomal abnormalities, and complications were associated with a significantly increased duration of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This difference persisted after adjusting for known risk factors for post-operative morbidity and mortality. Moreover, while the PLOS for our total cohort were similar to other reports for patients after repair of conotruncal defects 6, 13 , we found that those with intramural VSDs had a significantly longer PLOS compared to those with a non-intramural VSD or no VSD after surgery. This difference persisted after correcting for potential confounders.…”
Section: Discussionsupporting
confidence: 89%
“…This difference persisted after adjusting for known risk factors for post-operative morbidity and mortality. Moreover, while the PLOS for our total cohort were similar to other reports for patients after repair of conotruncal defects 6, 13 , we found that those with intramural VSDs had a significantly longer PLOS compared to those with a non-intramural VSD or no VSD after surgery. This difference persisted after correcting for potential confounders.…”
Section: Discussionsupporting
confidence: 89%
“…Birth weight has been described as a predictor of outcome after congenital heart surgery, in particular when the weight is less than 2.5 kg . In TOF, studies have shown that low birth weight is associated with length of hospital stay . Lower birth weight may reflect fetal health, placental heath, or a genetic basis .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, neonatal repair was independently associated with longer THD. Other studies have shown that neonatal repair for TOF is associated with increased circulatory support time, length of mechanical ventilation, greater use of postoperative inotropes, longer LOHS, and subsequent reoperations . The neonatal heart might be less “mature” and more vulnerable in the symptomatic neonate with TOF and thus less able to tolerate exposures such as cardiopulmonary bypass and ventriculotomy during surgical repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations